466 Development of a novel tocotrienol analogue, tocoflexol, as a radiomitigator - Shivangi Shrimali; Awantika Singh; Rajeshkumar Manian; Shraddha Thakkar; Darin E. Jones; Nukhet Aykin-Burns; Philip Breen; Cesar M. Compadre (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: We have designed an analogue of the Vitamin E tocotrienols called tocoflexol, which improves their pharmacokinetic limitations to make it an effective radiation medical countermeasure. Our goal is to demonstrate that tocoflexol is an effective radiomitigator in vivo when administered after exposure to lethal doses of total body irradiation. METHODS/STUDY POPULATION: Tocoflexol was designed using computational techniques to improve binding to ATTP, the key transporter that reduces the rate of elimination of tocols. In vitro studies compared the antioxidant and cell uptake properties to conventional tocotrienols. Next, we used a mouse model of lethal total body irradiation to evaluate its radioprotection efficacy (treating before radiation). To determine the optimal administration route for radiomitigation (treating after radiation), we will test oral and subcutaneous dosing. Mouse survival will be monitored for 30 days after irradiation. Sample tissues will be taken to evaluate the ability of tocoflexol to protect key organs from acute radiation syndrome. The bioavailability of tocoflexol will be evaluated in a rodent model. RESULTS/ANTICIPATED RESULTS: Known Results: Results show that tocoflexol has potent antioxidant properties and high cell uptake. When tocoflexol was administered 24 hours before exposure to lethal doses of radiation, tocoflexol-treated mice showed 100% survival. Anticipated Results: Because of its improved bioavailability and pharmacokinetic properties, we expect that tocoflexol will show radiomitigation efficacy when administered 24 hours after radiation, improving survival and protecting key organ systems from acute radiation syndrome. DISCUSSION/SIGNIFICANCE: There is an unmet need for safe and effective radiomitigators that can offer multi-organ protection and be rapidly administered in the event of nuclear emergencies. Demonstration of radiomitigation efficacy will position tocoflexol as a prime candidate to be developed into a nuclear medical countermeasure and stockpiled for emergencies.